Validation and Comparison of DEBQ and TEMS in Assessing Eating Behaviours in the Romanian Adult Population - Ana Maria Gal; Oana Dumitrascu; Andreea Gherasim; Otilia Nita; Alina Delia Popa; Laura Mihalache; Lidia Iuliana Arhire (Proceedings)
Non-communicable diseases are a major health burden worldwide, and they all share diet as common risk factor. In this context, understanding the complexity of eating behaviours can be useful both at the individual and population level for prevention and treatment. Foremost, there is a need for reliable and simple tools to assess eating behaviours, both for public health research and clinical practice. The aim of this study was to validate in Romanian and test by comparison two internationally popular questionnaires of eating behaviour: The Dutch Eating Behavior Questionnaire (DEBQ), which assesses emotional, external and restricted eating styles, and The Eating Motivation Survey (TEMS), short form, which investigates 15 determinants of food intake (taste, habits, need and hunger, health, convenience, pleasure, tradition, considerations related to the origin of food, social, price, appearance, weight control, social norms and social image). Methods: We tested (with the consent of the authors of the original questionnaires) the psychometric properties of the Romanian versions of DEBQ and TEMS on an adult general population and explored associations of eating behaviour with weight status with both questionnaires. Our study showed factor loads similar to the original version of the questionnaire for DEBQ and a very good internal validity (Cronbach's alpha fidelity coefficient greater than 0.8) for both DEBQ and TEMS. Emotional eating in DEBQ and items related to emotional eating in TEMS showed the strongest correlation with weight, but for all scales of DEBQ, there were further information given by TEMS. This study enables the use of the DEBQ and TEMS in Romania for the adult population. We also consider that the two questionnaires could be used together for developing more adequate strategies to reduce the burden of nutrition-related diseases.